PENGARUH PANDEMI COVID-19 TERHADAP PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK KELAS 3 DI SEKOLAH DASAR ISLAM TERPADU MUHAMMADIYAH DI KOTA CIREBON (Politeknik Kesehatan Kemenkes Bandung, 2021)
The COVID-19 pandemic has triggered various sectors to experience disruption, one of which is the dental and oral health service sector. Dental and oral health during the Corona virus pandemic has decreased. There are many factors that cause this to happen, ranging from the implementation of health protocols in the form of social distancing, many people who have lost their jobs thereby risking their oral health, increased sugar consumption during the Covid-19 pandemic, and lost motivation or willingness to maintain healthy teeth and teeth. mouth. Parents say Covid-19 is a barrier to giving children the dental care they need. The purpose of this study was to determine differences in dental and oral health maintenance behavior before and during the covid-19 pandemic. The sample in this study involved 57 parents or guardians of third grade students of SDIT Muhammadiyah Cirebon with total sampling technique. After that, the resulting data is processed by analysis using the Wilcoxon test. The results showed that there was an influence of the COVID-19 pandemic on the behavior of maintaining dental and oral health in grade 3 children, known as Asymp.Sig. (2-tailed) is worth 0.004. Conclusion: There is an Influence of the COVID-19 Pandemic on Dental and Oral Health Maintenance Behavior in Grade 3 Children